Methane Emissions from the Marcellus Shale in Southwestern Pennsylvania and Northern West Virginia Based on Airborne Measurements. Issue 3 (5th February 2019) - Ren, Xinrong; Hall, Dolly L.; Vinciguerra, Timothy; Benish, Sarah E.; Stratton, Philip R.; Ahn, Doyeon; Hansford, Jonathan R.; Cohen, Mark D.; Sahu, Sayantan; He, Hao; Grimes, Courtney; Fuentes, Jose D.; et al.
Abstract: Natural gas production in the United States has increased rapidly over the past decade, along with concerns about methane (CH4 ) fugitive emissions and its climate impacts. Quantification of CH4 emissions from oil and natural gas (O&NG) operations is important for establishing scientifically sound policies for mitigating greenhouse gases. We use the aircraft mass balance approach for three flight experiments in August and September 2015 to estimate CH4 emissions from O&NG operations over the southwestern Marcellus Shale. We estimate a mean CH4 emission rate as 21.2 kg/s with 28% coming from O&NG operations. The mean CH4 emission rate from O&NG operations was estimated to be 1.1% of total NG production. The individual best‐estimate emission rates from the three flight experiments ranged from 0.78 to 1.5%, with overall limits of 0% and 3.5%. These emission rates are at the low end of other top‐down studies, but consistent with the few observational studies in the Marcellus Shale region as well as the U.S. Environmental Protection Agency CH4 inventory. A substantial source of CH4 (~70% of observed CH4 emissions) was found to contain little ethane, possibly due to coalbed CH4 emitted either directly from coal mines or from wells drilled through coalbed layers in O&NG operations. Recent regulations requiring capture of gas from the completion‐venting step of hydraulic fracturing appear to have reduced the atmospheric release of CH4 . Our study suggests that for a 20‐year time scale, energy derived from the combustion of natural gas extracted from this region likely exerts a net climate benefit compared to coal. Plain Language Summary: In this study methane (CH4 ) emission rates were estimated for the southwest Marcellus Shale based on airborne observations. A mean emission rate of ~21 kg CH4 /s was observed from a 4, 200‐km 2 study area. A significant portion (~70%) of the emitted CH4 was found to originate likely from coalbeds. Our mean estimated emission rate of 1.1% of total natural gas production indicates a climate benefit of natural gas combustion compared to coal, but the full range includes values above the 2.4% break‐even point for the CH4 global warming potential over a 20‐year time horizon. Key Points: A CH4 emission rate of ~21 kg/s from a 4200 km 2 area of the southwestern Marcellus in 2015 with the bulk of the CH4 coming from coalbeds We estimate a mean CH4 emission rate of 1.1% of total natural gas production with a lower limit of 0% and an upper limit of 3.5% The mean emission rate indicates a climate impact of CH4 combustion below that of coal, but the full range includes values above this point